THE UNIFICATION OF THE ALBANIAN ALPHABET AND THE ROLE OF AUSTRIA - Sala, Kozeta; Shapllo, Elvira (European Scientific Journal, ESJ, 2014)
In the second half of the XIX century and the beginning of the XX century, Austria, known as Austro-Hungary since 1867, became Albania’s most powerful and supportive ally in the in the demanding process of establishing the Albanian state, the efforts to achieve its independence as well as to protect its territorial integrity within the boundaries settled by the London Conference of Ambassadors in 1913. The attitude of Austro- Hungary towards the Albanian national issue was a logical result as well as an integral part of a consequential policy adopted by them since centuries ago. Ultimately, this attitude would help Austro-Hungary to achieve one of its objectives as a political power with definite interests in the Balkans. The Albanian policy of Austro-Hungary in the second half of the XIX century and the beginning of the XX century was a major factor, which positively influenced the developments of the time at the most significant moments for Albania and the Albanians. One of those noteworthy moments was the Austro-Hungarian support and the exceptionally positive approach to the issue of the Unification of the Albanian Alphabet. Concerning the issue of the Unification of the Albanian Alphabet, Russia together with other chauvinistic Balkan countries on one side and Austro-Hungary on the other side had two diametrically opposed attitudes.